A Longitudinal Study Examining Dual Enrollment as a Strategy for Easing the Transition to College and Career for Emerging Adults. Issue 1 (February 2022) - Henneberger, Angela K.; Witzen, Heath; Preston, Alison M.
Successfully transitioning to adulthood requires a successful transition from high school into college or the workforce. Yet for many emerging adults, this transition is not successful, leading to disengagement from school and work. Dual enrollment, where high school students enroll in college coursework, may help to facilitate this important life transition. This study applied propensity score matching to statewide administrative data to investigate the effects of dual enrollment on college and early labor market outcomes. We found a significant effect of dual enrollment on 2-year and 4-year college enrollment, degree attainment, and early labor market earnings 6 years after high school, with stronger effects for students who are traditionally underrepresented (e.g., Black and Other race students and students eligible for free and reduced price meals). This study highlights the potential for targeting dual enrollment programs toward underrepresented students to improve the transition into college and the workforce for emerging adults.